Integration of Using Fintech and Social Media for The Business Sustainability in Pesantren - Syamsu, Nur; Sofyan, Syaakir; Aisya, Sitti; MD, Muthmainnah (EKONOMIKA SYARIAH : Journal of Economic Studies, 2022)
The urgency in utilizing fintech and social media in business to realize the Halal Value Chain (HVC) is paramount because it can provide added economic value for halal business actors, including Islamic boarding schools in the era of Society 5.0. This study aims to analyze the optimization of financial technology and social media integration in halal businesses managed by Islamic boarding schools to achieve the SDGs in the 5.0 era. This study uses phenomenology with data sources from Islamic boarding schools in Central Sulawesi. This research reveals that the integration relationship between fintech and social media highly depends on optimizing both. Factors driving the use of fintech and social media in Islamic boarding schools business consist of internal factors in the form of pesantren awareness of the importance of sustainable business activities and the vision of independence that exists in Islamic boarding schools. Furthermore, internal driving factors include the Covid-19 pandemic, market growth, digital market behavior, market growth, digital access, and customer behavior. Optimizing the use of social media in market mapping to see market demand trends has implications for Islamic boarding school business strategies in developing products.